A polymer electrolyte, a method for preparing the same, and a battery

CN118040038BActive Publication Date: 2026-10-20CHINA TOWER CO LTD +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410413133.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-07
Publication Date
2026-10-20
Estimated Expiration
2044-04-07

AI Technical Summary

Technical Problem

[0004]本发明公开了一种聚合物电解质、其制备方法及电池,以解决现有技术中聚偏二氟乙烯PVDF基聚合物固态电解质离子传导能力弱、聚合物分解反应而导致的电池循环性能不佳的问题

Benefits of technology

本发明涉及聚合物基固态锂金属电池的低温应用领域,通过利用(2-氰乙基)三乙氧基硅烷TEOSCN在聚偏二氟乙烯PVDF链中引入Si-O键,大大降低了聚偏二氟乙烯PVDF的Tg,从而增强了Li+沿聚合物链传导的能力。同时,高浓度-C≡N基团可抑制PVDF脱氢氟化对电极的损伤,进而实现耐低温的高稳定性锂金属固态电池。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118040038B_ABST
    Figure CN118040038B_ABST
Patent Text Reader

Abstract

The application relates to the low-temperature application field of a polymer-based solid-state lithium metal battery, and by introducing Si-O bonds in a polyvinylidene fluoride (PVDF) chain through (2-cyanoethyl)triethoxysilane TEOSCN, the Tg of the polyvinylidene fluoride (PVDF) is greatly reduced, thereby enhancing the ability of Li+ to conduct along the polymer chain. Meanwhile, the high-concentration-C≡N group can inhibit the damage of PVDF dehydrofluorination to the electrode, thereby realizing a low-temperature-resistant high-stability lithium metal solid-state battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of battery technology, and in particular to a polymer electrolyte, its preparation method, and a battery. Background Technology

[0002] The flammability of commercial organic liquid electrolytes and their incompatibility with lithium metal anodes pose significant safety hazards to the normal operation of batteries. The practical application of lithium metal batteries is hampered by the uncontrolled exothermic reaction between the active lithium metal and the organic liquid electrolyte. Solid-state electrolytes, which are safer and more reliable, are undoubtedly a better alternative to traditional commercial liquid electrolytes. Rechargeable solid-state batteries, composed of solid electrolytes and lithium metal anodes, have shown great promise in battery systems that improve energy density and safety, and are expected to break through the bottlenecks limiting the development of state-of-the-art lithium-ion batteries.

[0003] Inorganic solid electrolytes exhibit poor wettability to electrodes, leading to limitations in ion transport due to incompatibility between the electrolyte solid particles and the electrode interface. Polymer solid electrolytes combine the advantages of good interfacial wettability of liquid electrolytes with the high safety of inorganic solid electrolytes, ensuring long-term safe battery operation. However, polyvinylidene fluoride (PVDF)-based electrolytes exhibit significant rigidity at lower temperatures, resulting in weak ion conductivity and rapid capacity decay as temperature decreases. Furthermore, the severe dehydrogenation and fluorination reactions in PVDF-based polymer solid electrolytes significantly reduce the lifespan of polymer solid-state batteries. Summary of the Invention

[0004] This invention discloses a polymer electrolyte, its preparation method, and a battery, to solve the problems of weak ion conductivity and poor battery cycle performance caused by polymer decomposition reactions in existing polyvinylidene fluoride (PVDF)-based polymer solid electrolytes.

[0005] To achieve the above objectives, the embodiments in this specification adopt the following technical solutions: In a first aspect, a polymer electrolyte is provided, comprising: (2-cyanoethyl)triethoxysilane, polyvinylidene fluoride, and a lithium salt.

[0006] Optionally, the mass ratio of (2-cyanoethyl)triethoxysilane to polyvinylidene fluoride is 1:1 to 1:3.

[0007] Optionally, the lithium salt is one or a mixture of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bis(fluoromethanesulfonyl)imide (LiFSI), and lithium trifluoromethanesulfonate (LiCF3SO3).

[0008] Optionally, the polymer electrolyte is a solid or a liquid; When the polymer electrolyte is a liquid, the polymer electrolyte further includes a solvent, which is one or a mixture of N-methylpyrrolidone (NMP), N,N-dimethylformamide (DMF), and N,N-dimethylacetamide (DMAc).

[0009] Secondly, a method for preparing a polymer electrolyte is provided, comprising the following steps: (2-Cyanoethyl)triethoxysilane was added to a lithium salt solution containing polyvinylidene fluoride to obtain a polymer electrolyte.

[0010] Optionally, (2-cyanoethyl)triethoxysilane is added to a lithium salt solution containing polyvinylidene fluoride, stirred at room temperature for 3-6 hours, and then stirred at 60-80°C for 24-48 hours to obtain the polymer electrolyte.

[0011] Optionally, the method for preparing the lithium salt solution containing polyvinylidene fluoride includes the following steps: Polyvinylidene fluoride is dispersed in a solvent to obtain a mixture; Lithium salt is added to the mixture to obtain a lithium salt solution containing polyvinylidene fluoride.

[0012] Optionally, the mass ratio of the polyvinylidene fluoride to the solvent is 1:7 to 1:9.

[0013] Optionally, the solvent is one or a mixture of N-methylpyrrolidone (NMP), N,N-dimethylformamide (DMF), and N,N-dimethylacetamide (DMAc).

[0014] Optionally, the mass ratio of the polyvinylidene fluoride to the lithium salt is 2 to 6:1.

[0015] Thirdly, a battery is provided, the battery comprising the polymer electrolyte mentioned in the first aspect or the polymer electrolyte prepared by the preparation method described in the second aspect.

[0016] The above-described technical solutions adopted in the embodiments of this application can achieve the following beneficial effects: This invention relates to the low-temperature application of polymer-based solid-state lithium metal batteries. By introducing Si-O bonds into the polyvinylidene fluoride (PVDF) chain using (2-cyanoethyl)triethoxysilane (TEOSCN), the thermal conductivity (Tg) of PVDF is significantly reduced, thereby enhancing the ability of Li+ to conduct along the polymer chain. Simultaneously, the high concentration of -C≡N groups can suppress the damage to the electrodes caused by PVDF dehydrofluorination, thus achieving a high-stability lithium metal solid-state battery with low-temperature resistance. Attached Figure Description

[0017] The accompanying drawings, which are included to provide a further understanding of this application and form part of this application, illustrate exemplary embodiments of this application and are used to explain this application, but do not constitute an undue limitation of this application. In the drawings: Figure 1 The graph shows the cycle performance of the lithium symmetric battery of Example 1 of the present invention at a low temperature of -20°C and 0.2 mA / 0.2 mAh. Figure 2 The graph shows the cycle performance of the lithium-sulfur full battery of Example 1 of the present invention at a low temperature of -20°C and 0.2C. Detailed Implementation

[0018] To make the objectives, technical solutions, and advantages of this application clearer, the technical solutions of this application will be clearly and completely described below in conjunction with specific embodiments and corresponding drawings. Obviously, the described embodiments are only a part of the embodiments of this application, and not all of them. Based on the embodiments in this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.

[0019] According to one embodiment of this application, a polymer electrolyte is provided, comprising: (2-cyanoethyl)triethoxysilane, polyvinylidene fluoride, and lithium salt.

[0020] The Si-O bonds in (2-cyanoethyl)triethoxysilane TEOSCN significantly reduce the Tg of PVDF, thereby enhancing the low-temperature resistance of the solid electrolyte. Simultaneously, the high concentration of Si-O groups can react with acidic byproducts in the electrolyte, preventing their corrosion of the negative electrode and improving its cycle stability. The -C≡N groups, located in the lowest electrostatic potential region of the molecule, facilitate the dissociation of lithium salts. The π-π coupling of the -C≡N groups improves the oxidative stability of the polymer matrix, inhibits the damage to the electrode caused by PVDF dehydrofluorination, and ensures the long-cycle performance of lithium metal batteries. The introduction of TEOSCN, containing both Si-O bonds and -C≡N groups, ultimately enables the PVDF electrolyte to exhibit both low-temperature resistance and corrosion resistance.

[0021] In the embodiments described in this specification, the (2-cyanoethyl)triethoxysilane and the polyvinylidene fluoride can be mixed in any proportion, and the present invention does not impose any limitation on this. Optionally, the mass ratio of the (2-cyanoethyl)triethoxysilane to the polyvinylidene fluoride is 1:1 to 1:3.

[0022] In the embodiments of this specification, the lithium salt can be any one or more reagents, as long as they enable the electrolyte to conduct lithium ions; the present invention does not impose any limitations on this. Optionally, the lithium salt in the lithium salt solution containing polyvinylidene fluoride is one or a mixture of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bis(fluoromethanesulfonyl)imide (LiFSI), and lithium trifluoromethanesulfonate (LiCF3SO3).

[0023] In the embodiments of this specification, the polymer electrolyte is either a solid or a liquid. When the polymer electrolyte is a liquid, it further includes a solvent, which can be any one or more reagents capable of dissolving (2-cyanoethyl)triethoxysilane, polyvinylidene fluoride, and lithium salt; this invention is not limited in this regard. Optionally, the solvent in the lithium salt solution containing polyvinylidene fluoride is one or a mixture of N-methylpyrrolidone (NMP), N,N-dimethylformamide (DMF), and N,N-dimethylacetamide (DMAc).

[0024] According to one embodiment of this application, a method for preparing a polymer electrolyte is provided, comprising the following steps: (2-Cyanoethyl)triethoxysilane was added to a lithium salt solution containing polyvinylidene fluoride, stirred, and then heated and stirred to obtain a polymer electrolyte.

[0025] In the embodiments described in this specification, the stirring time and temperature are not limited by the present invention, as long as the mixing effect can be achieved. Optionally, after adding (2-cyanoethyl)triethoxysilane to a lithium salt solution containing polyvinylidene fluoride, the mixture is first stirred at room temperature for 3-6 hours, and then stirred for another 24-48 hours at 60-80°C to obtain a polymer electrolyte.

[0026] In the embodiments of this specification, the preparation method of the lithium salt solution containing polyvinylidene fluoride includes the following steps: Polyvinylidene fluoride is dispersed in a solvent to obtain a mixture; Lithium salt is added to the mixture to obtain a lithium salt solution containing polyvinylidene fluoride.

[0027] In the embodiments of this specification, the polyvinylidene fluoride and the solvent can be mixed in any proportion, and the present invention does not impose any limitation on this. Optionally, the mass ratio of polyvinylidene fluoride to solvent is 1:7 to 1:9. The stirring time for dispersing polyvinylidene fluoride in the solvent can be selected as 24 to 48 hours.

[0028] In the embodiments described in this specification, the polyvinylidene fluoride and the lithium salt can be mixed in any proportion, and the present invention does not impose any limitation on this. Optionally, the mass ratio of the polyvinylidene fluoride to the lithium salt is 2~6:1. The stirring time for adding the lithium salt to the mixture can be selected as 24~48 hours.

[0029] According to one embodiment of this application, a battery is provided, the battery comprising the polymer electrolyte mentioned above or the polymer electrolyte prepared above. Specifically, a use of the polymer electrolyte is provided, specifically its use in lithium-symmetric batteries and lithium-sulfur batteries.

[0030] The resulting batteries can be used in base station environments with low temperatures, such as mountainous areas and plateaus, to improve low-temperature capacity, lifespan, and safety stability, while reducing costs associated with manual maintenance and risk protection.

[0031] Compared to other solid-state electrolytes, polymer electrolytes, due to their flexibility, can form better interfacial contact with electrodes, which is beneficial for ion conduction. Adding liquid components to the polymer not only enhances the wettability of the polymer electrolyte to the electrode but also modulates the physicochemical properties of the electrolyte. TEOSCN, a (2-cyanoethyl)triethoxysilane with silicon-based functional groups, introduces multiple functional groups into the polymer solid-state electrolyte, reducing the Tg of the polymer electrolyte, improving its oxidative stability, and mitigating the damage to the electrode caused by polymer dehydrofluorination, thereby ensuring the long-cycle characteristics of the lithium metal battery. The introduction of the (2-cyanoethyl)triethoxysilane component with a low Tg and its polar interaction with polyvinylidene fluoride not only reduces the material's Tg but also enhances electrolyte stability through the silicon-based functional groups carried by TEOSCN, ultimately achieving a low-temperature resistant, highly stable quasi-solid-state polymer lithium metal battery.

[0032] This invention employs a PVDF-based electrolyte, which can mitigate the safety issues of lithium metal batteries caused by the use of flammable liquid electrolytes. Introducing (2-cyanoethyl)triethoxysilane into the electrolyte can alleviate the harmful effects of PVDF-based electrolyte dehydrofluorination on electrolyte stability and electrodes. The PVDF-based electrolyte modified with (2-cyanoethyl)triethoxysilane can reduce the low-temperature tolerance range of quasi-solid-state batteries and enhance their cycle stability. This invention directly uses PVDF as the polymer matrix and specifically introduces (2-cyanoethyl)triethoxysilane in liquid molecular form. Through the polar interaction between Si-O bonds and CF bonds, it promotes PVDF chain expansion, increases chain segment flexibility, prevents the formation of crystalline regions, and thus lowers the material's Tg, allowing it to maintain high mobility at lower temperatures. The (2-cyanoethyl)triethoxysilane used needs to be uniformly dissolved in NMP and then fully contacted with the PVDF molecular chains in liquid molecular form to achieve the polar interaction between Si-O bonds and CF bonds at the microscopic level, promoting PVDF chain expansion, preventing crystalline region formation, and promoting lithium-ion conduction at low temperatures. Furthermore, the high concentration of Si-O groups in full contact with the PVDF chains can remove acidic substances formed in the electrolyte, while the π−π coupling of -C≡N groups improves the oxidative stability of the polymer matrix, inhibits damage to the electrodes caused by PVDF dehydrofluorination, and ensures long-cycle performance of the lithium metal battery at lower temperatures.

[0033] The technical solutions provided by the various embodiments of this application are described in detail below with reference to the accompanying drawings.

[0034] Example 1: A method for preparing a polymer electrolyte is provided, comprising the following steps: (1) Disperse 1.5g of polyvinylidene fluoride evenly in NMP solvent, stir at 250rpm to mix evenly, and stir for 24h to obtain a mixture, wherein the mass ratio of polyvinylidene fluoride to solvent is 1:7. (2) Weigh the lithium salt according to the mass ratio of polyvinylidene fluoride to lithium salt of 4:1, add the lithium salt to the mixture, and continue stirring for 24 hours to obtain a lithium salt solution containing polyvinylidene fluoride. (3) Add (2-cyanoethyl)triethoxysilane to a lithium salt solution containing polyvinylidene fluoride, stir at room temperature for 3 h, and then continue stirring at 80 °C for 24 h to obtain a polymer electrolyte, wherein the mass ratio of (2-cyanoethyl)triethoxysilane to polyvinylidene fluoride in the lithium salt solution containing polyvinylidene fluoride is 1:3.

[0035] Example 2: A method for preparing a polymer electrolyte is provided, comprising the following steps: (1) Disperse 1.5g of polyvinylidene fluoride evenly in NMP solvent, stir at 250rpm to mix evenly, and stir for 36h to obtain a mixture, wherein the mass ratio of polyvinylidene fluoride to solvent is 1:9. (2) Weigh the lithium salt according to the mass ratio of polyvinylidene fluoride to lithium salt of 2:1, add the lithium salt to the mixture, and continue stirring for 36 hours to obtain a lithium salt solution containing polyvinylidene fluoride. (3) Add (2-cyanoethyl)triethoxysilane to a lithium salt solution containing polyvinylidene fluoride, stir at room temperature for 6 h, and then continue stirring at 70 °C for 36 h to obtain a polymer electrolyte, wherein the mass ratio of (2-cyanoethyl)triethoxysilane to polyvinylidene fluoride in the lithium salt solution containing polyvinylidene fluoride is 1:1.

[0036] Example 3: A method for preparing a polymer electrolyte is provided, comprising the following steps: (1) Polyvinylidene fluoride is uniformly dispersed in NMP solvent and stirred at 250 rpm for 48 h to obtain a mixture, wherein the mass ratio of polyvinylidene fluoride to solvent is 1:8. (2) Weigh the lithium salt according to the mass ratio of polyvinylidene fluoride to lithium salt of 6:1, add the lithium salt to the mixture, and continue stirring for 48 hours to obtain a lithium salt solution containing polyvinylidene fluoride. (3) Add (2-cyanoethyl)triethoxysilane to a lithium salt solution containing polyvinylidene fluoride, stir at room temperature for 4 h, and then continue stirring at 60 °C for 48 h to obtain a polymer electrolyte, wherein the mass ratio of (2-cyanoethyl)triethoxysilane to polyvinylidene fluoride in the lithium salt solution containing polyvinylidene fluoride is 1:2.

[0037] Comparative Example 1: A method for preparing a polymer electrolyte is provided, comprising the following steps: (1) Disperse 1.5g of polyvinylidene fluoride evenly in NMP solvent, stir at 250rpm to mix evenly, and stir for 24h to obtain a mixture, wherein the mass ratio of polyvinylidene fluoride to solvent is 1:7. (2) Weigh the lithium salt according to the mass ratio of polyvinylidene fluoride to lithium salt of 4:1, add the lithium salt to the mixture, and continue stirring for 24 hours to obtain the polymer electrolyte.

[0038] The polymer electrolytes obtained in Examples 1-3 and Comparative Example 1 were uniformly coated onto a clean glass plate surface, then vacuum dried at 60°C, and pressed into tablets to obtain the electrolyte. The coating thickness was 500 nm, and the thickness after drying was approximately 100 μm. The obtained electrolytes were used to assemble lithium symmetric batteries and lithium-sulfur batteries.

[0039] The lithium symmetric batteries obtained in Examples 1-3 and Comparative Example 1 were tested at a low temperature of -20°C, with a cycle life of 0.2 mA / 0.2 mAh, a cycle time of 2 h per cycle, and a stable cycle time of up to 800 h. The lithium-sulfur full cells obtained in Examples 1-3 and Comparative Example 1 were tested at a low temperature of -20°C, with a cycle life of 0.2 C, and a remaining capacity of 500 mAh / g after 115 cycles.

[0040]

[0041] The above description is merely an embodiment of this application and is not intended to limit the scope of this application. Various modifications and variations can be made to this application by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this application should be included within the scope of the claims of this application.

Claims

1. A polymer electrolyte, characterized in that, include: (2-Cyanoethyl)triethoxysilane, polyvinylidene fluoride, lithium salt and solvent; The (2-cyanoethyl)triethoxysilane interacts polarly with the polyvinylidene fluoride. The mass ratio of (2-cyanoethyl)triethoxysilane to polyvinylidene fluoride is 1:1 to 1:3; The mass ratio of the polyvinylidene fluoride to the lithium salt is 2~6:1; The lithium salt is one or a mixture of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bis(trifluoromethanesulfonyl)imide (LiFSI), and lithium trifluoromethanesulfonate (LiCF3SO3). The method for preparing the polymer electrolyte includes the following steps: (2-Cyanoethyl)triethoxysilane was added to a lithium salt solution containing polyvinylidene fluoride, and the mixture was stirred at room temperature for 3-6 hours, and then stirred at 60-80°C for 24-48 hours to obtain the polymer electrolyte.

2. The polymer electrolyte according to claim 1, characterized in that, The solvent is one or a mixture of N-methylpyrrolidone (NMP), N,N-dimethylformamide (DMF), and N,N-dimethylacetamide (DMAc).

3. A method for preparing the polymer electrolyte according to any one of claims 1-2, characterized in that, Includes the following steps: (2-Cyanoethyl)triethoxysilane was added to a lithium salt solution containing polyvinylidene fluoride to obtain a polymer electrolyte; The method for preparing the lithium salt solution containing polyvinylidene fluoride includes the following steps: Polyvinylidene fluoride is dispersed in a solvent to obtain a mixture; Lithium salt is added to the mixture to obtain a lithium salt solution containing polyvinylidene fluoride.

4. The preparation method according to claim 3, characterized in that, The mass ratio of the polyvinylidene fluoride to the solvent is 1:7 to 1:9; and / or, The solvent is one or a mixture of N-methylpyrrolidone (NMP), N,N-dimethylformamide (DMF), and N,N-dimethylacetamide (DMAc).

5. A battery, characterized in that, The battery comprises a polymer electrolyte according to any one of claims 1-2 or a polymer electrolyte prepared by any one of claims 3-4.

Citation Information

Patent Citations

  • Method for improving ionic conductivity of polymer solid electrolyte of lithium ion battery, solid electrolyte prepared by method, and battery

    CN114976231A

  • High-voltage electrolyte suitable for nickel lithium manganate material

    CN115395101A

  • Electrolyte for lithium ion battery, lithium ion battery and vehicle

    CN116742136A

  • Lithium supplement method and device for negative pole piece of lithium ion battery

    CN117728051A